A Comparative Analysis of JOURNEY Metaphors in Marketing English - Wang, Jinxiao (Advances in Social Sciences Research Journal, 2020)
Metaphor is a powerful cognitive tool that can help to transmit marketing concept, and form effective marketing strategies. The conceptual metaphor of MARKETING IS JOURNEY has been viewed as a significant deep metaphor in the field of marketing all along. Based on five authoritative marketing textbooks and research articles of three high influencing factor journals in 2016, this paper builds a corpus of three million words. By virtue of previous studies, the author makes a check-list, and intends to explore the usage of JOURNEY metaphors in marketing English with the help of “Metaphor Identification Process (MIP)” (Steen at al. 2010) from the perspective of Conceptual Metaphor Theory. The results show that: (1) the productivity of CMTB is 64,209, which is much higher than that of CMJA, 32,184; (2) Themes of obstacles & facilitators, directions of journey, uphill & downhill, as well as fast & slow progress of journey are widely employed in marketing English, with marketing research articles laying more focus on the theme of directions of journey than textbooks; (3) similarities and differences between them can be explained by the contextual factors of field, tenor, and mode. Further implications includes that it can help to appeal to further revision of established marketing textbooks, for that the most cutting-edge metaphorical expressions, e.g., “memory block”, should be included in textbooks for better catching up with the latest development in the field of marketing.